Genome-Wide Identification, Evolutionary Analysis and Expression Profiles of LATERAL ORGAN BOUNDARIES DOMAIN Gene Family in Lotus japonicus and Medicago truncatula - Yang, Tianquan (PLoS One, 2016)
The LATERAL ORGAN BOUNDARIES DOMAIN (LBD) gene family has been well-studied in Arabidopsis and play crucial roles in the diverse growth and development processes including establishment and maintenance of boundary of developmental lateral organs. In this study we identified and characterized 38 LBD genes in Lotus japonicus (LjLBD) and 57 LBD genes in Medicago truncatula (MtLBD), both of which are model legume plants that have some specific development features absent in Arabidopsis. The phylogenetic relationships, their locations in the genome, genes structure and conserved motifs were examined. The results revealed that all LjLBD and MtLBD genes could be distinctly divided into two classes: Class I and II. The evolutionary analysis showed that Type I functional divergence with some significantly site-specific shifts may be the main force for the divergence between Class I and Class II. In addition, the expression patterns of LjLBD genes uncovered the diverse functions in plant development. Interestingly, we found that two LjLBD proteins that were highly expressed during compound leaf and pulvinus development, can interact via yeast two-hybrid assays. Taken together, our findings provide an evolutionary and genetic foundation in further understanding the molecular basis of LBD gene family in general, specifically in L. japonicus and M. truncatula.